The Exception of Unconstitutionality of Laws Mechanism in the Light of the Latest Developments a Comparative Study - Algeria and Morocco - Guerses, Maroua; Boukouba, Khaled (Journal of Legal Studies and Researches, 2022)
We aim through this study, to shed light on the concept of the exception mechanism and the procedures followed in Algeria and Morocco where we conclude that they are largely identical, especially since the goal is the same with slight differences in the wording and terminology used and in naming constitutional institutions.